Hepatitis B virus X gene induces human telomerase reverse transcriptase mRNA expression in cultured normal human cholangiocytes - Zou, Sheng-Quan (World J Gastroenterol, 2004)
AIM: To study the transcriptional regulation of human telomerase reverse transcriptase (hTERT) mRNA in normal human cholangiocytes (HBECs) after hepatitis B virus X (HBx) gene transfection and to elucidate the possible mechanism of HBV infection underlying cholangiocarcinoma. METHODS: HBECs were cultured in vitro and co-transfected with a eukaryotic expression vector containing the HBx coding region and a cloning vector containing coding sequences of enhanced green fluorescent protein (EGFP) using lipid-mediated gene transfer. The transfection efficiency was determined by the expression of EGFP. The expressions of hTERT mRNA and HBx protein in HBECs were detected by RT-PCR and immunocytochemical stain, respectively. RESULTS: The transfection efficiencies were about 15% for both HBx gene expression plasmid and empty vector. No hTERT mRNA was expressed in HBECs when transfected with OPTI-MEM medium and empty vector, but a dramatic increase was observed for hTERT mRNA expression in HBECs when transfected with HBx expression vector. HBx protein was only expressed in HBECs when transfected with HBx expression vector. CONCLUSION: HBx transfection can activate the transcriptional expression of hTERT mRNA. Cis-activation of hTERT mRNA by HBx gene is the primary mechanism underlying the proliferation, differentiation and tumorigenesis of biliary epithelia.